Managing for Caribou Survival in a Partitioned Habitat - Cumming, H.G. (Rangifer, 1996)
Forest management guidelines for woodland caribou (Rangifer tarandus caribou) in Ontario need to be re-examined in light of the finding that caribou partition habitat with moose (Alces alces), partly to find virtual refuges from predation by gray wolves (Canis lupus). Forest-wide guidelines seem inappropriate for a species that is widely scattered and little known. Management should concentrate on and around currently used virtual refuges to ensure their continued habitability. Cutting these areas may force the caribou into places with higher densities of predators; winter use of roads might bring poachers, increased wolf entry, and accidents. A proposal for 100 km2 clear-cuts scheduled over 60+ years across the forest landscape would probably minimize moose/wolf densities in the long run as intended, but because of habitat partitioning might forfeit any benefits to caribou in the short-term. Sharply reducing moose densities near areas where caribou have sought refuge might incline wolves to switch to caribou. Cutting beyond caribou winter refuge areas should aim at maintaining current moose densities to prevent wolves from switching prey species. Operations level manipulation of the forest around each wintering area should provide winter habitat for the future, while treatment replications with controls across the whole forest would provide reliable knowledge about which approaches work best. The remainder of the forest should be managed to maintain suitable densities of all other species.